A method for reducing the influence of measuring distance on infrared thermal imager temperature measurement accuracy. (5th May 2016) - Zhang, Yu-cun; Chen, Yi-ming; Fu, Xian-bin; Luo, Cheng
Highlights: Three aspects caused by measuring distance are analyzed, respectively. The theory formulas for reducing the influence of measuring distance are proposed. The formula can reduce the influence of measuring distance effectively. Abstract: In order to improve the temperature measurement accuracy of infrared thermal imager, aiming at the influence of measuring distance on measurement accuracy, a method for reducing the influence of measuring distance is proposed in this paper. First, the three aspects influence principles containing angular field of infrared thermal imager, the contrast between tested object temperature and environmental temperature, and the atmospheric transmittances caused by measuring distance are analyzed. Second, based on the influence principle of measuring distance on measurement accuracy, three methods for reducing the influence on above three aspects are proposed, respectively. Theory formula of reducing the influence on above three aspects at the same time on infrared thermal imager measurement accuracy is obtained. Finally, in order to verify the feasibility of this theory formula, an experiment about a blackbody in different distance is done. Then, the measured temperature of blackbody is compared with calculated temperature after using the formula proposed in this paper. The experiment results show that this method can reduce the influence of measuring distance on infrared thermal imager temperature measurement accuracy effectively.